Avaliação de inseticidas no controle de Sitophilus oryzae (Linnaeus) (Coleoptera, Curculionidae) e Rhyzopertha dominica (Fabricius) (Coleoptera, Bostrichidae) em trigo armazenado - Furiatti,Rui S. (1999)
The efficiency of insecticides against Sitophilus oryzae (Linnaeus, 1763) (Coleoptera, Curculionidae) and Rhyzopertha dominica (Fabricius, 1792) (Coleoptera, Bostrichidae) was determined exposing them to treated wheat in laboratory. Each plot, which was composed by 1.2 kg of wheat grain, was treated with 5 ml of the concentration/kg of wheat using a propelling air atomizer. Fifteen days after treatment 50 g samples of the grain were taken, from each plot, placed in plastic jars into which 10 adult insects of each species were released. This was repeated every 30 days until 165 days after treatment. The number of dead insects was counted 15 days after each infestation thus the evaluations were made at 30, 60, 90, 120, 150 and 180 days after the insecticide application. Esfenvalerate+fenitrothion+pyperonil butoxide (0,375+7,5+3,0 and 0,5+10,0+4,0 g a.i./t), fenitrothion+esfen-valerate (7,5+0,375 and 10,0+0,375 g a.i./t), fenitrothion+synergised deltamethrin (7,5+0,375 g a.i./t) and fenitrothion (7,5 g a.i./t) were effective against Sitophilus oryzae until 180 days after treatment. Esfenvalerate+fenitrothion+pyperonil butoxide (0,5+10,0+4,0 g a.i./t), fenitrothion+esfenvalerate (7,5+0,375 and 10,0+0,375 g a.i./t), fenitrothion+synergised deltamethrin (7,5+0,375 g a.i./t) were effective against R. dominica until 180 days after treatment. Synergised deltamethrin (0,375 g a.i./t) was effective against S. oryzae until 150 days and against R. dominica until 120 days after treatment. Esfenvalerate (0,5 g a.i./t) was ineffective against S. oryzae and effective until 60 days after treatment against R. dominica. Fenitrothion (7,5 g a.i./t) was ineffective against R. dominica. The use of mixtures of organophosphorus plus pyrethroids were more effective against S. oryzae and R. dominica when compared with these insecticides used alone.